Multicopper oxidase-1 is a ferroxidase essential for iron homeostasis in Drosophila melanogaster - Lang, Minglin; Braun, Caroline L.; Kanost, Michael R.; Gorman, Maureen J. (My University, 2012)
Multicopper ferroxidases catalyze the oxidation of ferrous iron to ferric iron. In yeast and algae, they participate in cellular uptake of iron; in mammals, they facilitate cellular efflux. The mechanisms of iron metabolism in insects are still poorly understood, and insect multicopper ferroxidases have not been identified. In this paper we present evidence that Drosophila melanogaster multicopper oxidase-1 (MCO1) is a functional ferroxidase. We identified candidate iron binding residues in the MCO1 sequence and found that purified recombinant MCO1 oxidizes ferrous iron. An association between MCO1 function and iron homeostasis was confirmed by two observations: RNAi-mediated knockdown of MCO1 resulted in decreased iron accumulation in midguts and whole insects, and weak knockdown increased the longevity of flies fed a toxic concentration of iron. Strong knockdown of MCO1 resulted in pupal lethality, indicating that MCO1 is an essential gene. Immunohistochemistry experiments demonstrated that MCO1 is located on the basal surfaces of the digestive system and Malpighian tubules. We propose that MCO1 oxidizes ferrous iron in the hemolymph and that the resulting ferric iron is bound by transferrin or melanotransferrin leading to iron storage, iron withholding from pathogens, regulation of oxidative stress and/or epithelial maturation. These proposed functions are distinct from those of other known ferroxidases Given that MCO1 orthologs are present in all insect genomes analyzed to date, this discovery is an important step toward understanding iron metabolism in insects.
Keywords: Biological sciences; Genetics; Multicopper ferroxidases; Drosophila melanogaster